Influence of Service Quality and Promotion Towards Customer Interests in Saving Sari Giri Sedana Cooperative in Badung District - Novita, Ni Kadek Ari; Yudhaningsih, Ni Made; Pratiwi, Komang Asri (International Journal of Management and Business Intelligence, 2024)
This research is motivated by the phenomenon of decreasing customer interest in saving at the Sari Giri Sedana Cooperative. This research aims to examine the influence of service quality and promotion on customers' interest in saving at the Sari Giri Sedana Cooperative in Badung Regency. This research uses explanatory research with a quantitative approach. The population in this study was 903 people and the sample size in this study was 90 customers at the Sari Giri Sedana Cooperative. Data collection methods in this research are observation, interviews and questionnaires, with a Likert scale. The results of this research show that the results of the t test calculation show that service quality and promotion show a significance level of 0.021 and 0.022 <0.05, meaning that, partially, service quality and promotion have a significant influence on interest in saving. The results of the F test show that the quality of service and promotion shows a significance level of 0.000 < 0.05. This means that simultaneously the quality of service and promotion has a significant influence on interest in saving at the Sari Giri Sedana Cooperative in Badung Regency. The Durbin-Watson determination test results of 1.907 indicate that the model does not experience significant autocorrelation problems.    Suggestions for cooperatives in this research are to provide immediate, accurate and satisfactory services to customers because they have the lowest scores on the results of the questionnaire that has been distributed.